2006
DOI: 10.1007/s00442-006-0502-4
|View full text |Cite
|
Sign up to set email alerts
|

Population and clonal level responses of a perennial grass following fire in the northern Chihuahuan Desert

Abstract: Relationships involving fire and perennial grasses are controversial in Chihuahuan Desert grasslands of southern New Mexico, USA. Research suggests that fire delays the resprouting of perennial grasses well after two growing seasons. However, such results are confounded by livestock grazing, soil erosion, and drought. Additionally, post-fire grass responses may depend on initial clone size. We evaluated the effects of fire, grazing, and clone size on Bouteloua eriopoda (black grama) in southern New Mexico gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Reichmann, unpublished data). See Drewa et al (2006) for additional details on vegetation and soils at the site.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reichmann, unpublished data). See Drewa et al (2006) for additional details on vegetation and soils at the site.…”
Section: Methodsmentioning
confidence: 99%
“…Plots were 2.5 £ 2.5 m, and each was centered around a single mature mesquite shrub that was similar in size to other mesquite on this ecological site (mean height 0.5 m, canopy diameter 1.1 m; Drewa 2003). Shrubs were surrounded by black grama (mean basal area 11.48 cm 2 ; Drewa et al 2006); black grama individuals selected for measurements were >0.75 m from plot edges. Reductions in PPT were achieved via passive rainout shelters; supplementation was achieved via a sprinkler irrigation system.…”
Section: Methodsmentioning
confidence: 99%
“…(Drewa and Havstad, 2001;Valone and Kelt, 1999) and other vegetation (McGlone and Huenneke, 2004). However, responses of B. eriopoda to fire evaluated at the clonal scale showed a reduction in basal area and cover, but overall survivorship was dependent upon clone size, large clones having increased survivorship in comparison to small clones (Drewa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Drewa et al (2006) suggested that the patterns of precipitation immediately following fire may be a considerable factor in regrowth and recovery. Precipitation event size and frequency in post-fire conditions may substantially alter soil water recharge (Noy-Meir, 1973;Reynolds et al, 2004), ultimately affecting aboveground vegetation and post-fire recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Parmenter (2008) found that aboveground cover of B. eriopoda required 7-10 years to return to pre-fire abundance following a management burn. However, if large amounts of precipitation follow a burn, B. eriopoda canopy height can be equivalent in both burned and unburned areas after as little as one year of regrowth (Drewa et al 2006), but such conditions are rare. Just as favorable conditions can decrease recovery time, drought or grazing likely delay regeneration of B. eriopoda and other perennial grasses following disturbance (Reynolds and Bohning 1956, Cable 1967, Drewa et al 2006.…”
Section: Introductionmentioning
confidence: 99%